The use of L1 as a writing strategy in L2 writing tasks - Youngran Kim; Hyunsook Yoon (Penerbit UKM, 2014)
Numerous studies have investigated how students integrate L1 for the function of acquiring L2 writing proficiency. However, there is still no consensus that relates the degree of L1 use and various writing strategies in L2 writing to student proficiency levels and writing genres or writing tasks. The present study explored these issues over the course of 14 weeks with nine Korean university students of three different proficiency levels performing six writing tasks in two genres. The data were collected from the students‟ think-aloud protocols and retrospective interviews. The think-aloud and interview data were analyzed to examine the students‟ use of L1 during the L2 writing. The think-aloud protocols were also coded into their functions for what purposes each language type was used. The results showed that lower level students used their L1 more than the advanced students, but all students used L1 to different degrees depending on each task. In other words, the students reacted differently in accordance with task familiarity and the relative ease or difficulty of the task. The study also found that there was no consistent relationship between language proficiency and the types of writing strategies the students used in L2 composition. On the other hand, this study showed that although the types of writing strategies the students employed were similar, the students of various proficiency levels applied L1 strategies to their writing in different ways. The findings showed that L1 use in L2 writing can play an encouraging role for both the ideational and compensatory purposes, suggesting that the strategic use of L1 can contribute to improvement in L2 composition. The paper discusses that writing instruction should focus more on the topics of how to use writing strategies as well as what writing strategies to use.